PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR KOGNITIF IPA KELAS X AKL B SMKN 1 SEBATIK BARAT - Ali Ali; Sujud Sujud (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
The learning that is most often found when making observations in schools is learning that still does not involve students to learn actively. Students as a whole have not been actively involved in the learning process and the teacher becomes the centre of information, in this case, achieving the expected learning objectives. One of the efforts to direct students to be actively involved in the learning process is by implementing a scientific-based learning model, namely Problem Based Learning (PBL). In Problem Based Learning (PBL) learning syntax, students are oriented to a problem to be solved in groups by way of discussion. With this problem, students can develop their reasoning and critical thinking skills so that the final results achieved will increase learning outcomes at the cognitive level. This study aims to determine the increase in critical thinking skills and cognitive learning outcomes of students. The results of the research that have been done indicate that the application of the Problem Based Learning model can improve students' critical thinking skills and cognitive learning outcomes. Keywords: Problem Based Learning, Critical Thinking Skill, Cognitive Learning OutcomeImplementation of Problem-Based Learning to Increasing The Critical Thinking Skill and Cognitive Learning Outcome in Science Course in Class X AKL B SMKN 1 Sebatik Barat